Markers of Cardiovascular Health in Older Adults with and Without Chronic Low Back and Radicular Leg Pain: A Comparative Analysis. Issue 6 (15th February 2021) - Coyle, Peter C; O'Brien, Victoria A; Edwards, David G; Pohlig, Ryan T; Hicks, Gregory E
Abstract: Objectives: There is considerable overlap in risk profiles between chronic low back pain with radiculopathy (CLBPR) and cardiovascular health among older adults; obesity and smoking are related to both conditions and may largely drive the potential relationship. We sought to explore the impact of CLBPR on cardiovascular health outcomes, independent of body mass index (BMI) and current smoking status. Methods: Age- and sex-matched older adults (60–85 years of age) with (n = 21) and without (n = 21) CLBPR were recruited. Current smokers were excluded. Blood samples were collected to measure cholesterol levels and pro-inflammatory markers (i.e., C-reactive protein and interleukin-6). Vascular endothelial function, a marker of cardiovascular health, was evaluated by measuring brachial artery flow-mediated dilation (FMD). General linear models with multifactorial designs were evaluated; group membership, BMI, education, and their respective two-way interaction terms were included as independent variables. Results: Older adults with CLBPR had significantly higher BMIs ( P = 0.004) and lower educational levels ( P = 0.013) than did those without pain. There was a significant group-by-education interaction effect ( P = 0.049) for endothelial function. Older adults without pain who were highly educated had higher FMD values, indicating better endothelial function (9.2%), whereas the following combinations all had lower FMD values: no pain plus low education, CLBPR plus high education, and CLBPR plus low education (5.9%, 6.1%, and 6.6%, respectively). Conclusions: Among older adults, CLBPR is linked with worse endothelial function, regardless of educational level and independent of BMI and smoking. These findings suggest that older adults with CLBPR may be at a higher risk of cardiovascular disease.